2018
DOI: 10.2147/mder.s162854
|View full text |Cite
|
Sign up to set email alerts
|

Design and preliminary validation of a mobile application-based expert system to facilitate repair of medical equipment in resource-limited health settings

Abstract: BackgroundOne of the greatest barriers to safe surgery is the availability of functional biomedical equipment. Biomedical technicians play a major role in ensuring that equipment is functional. Following in-field observations and an online survey, a mobile application was developed to aid technicians in troubleshooting biomedical equipment. It was hypothesized that this application could be used to aid technicians in equipment repair, as modeled by repair of a pulse oximeter.MethodsTo identify specific barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It is estimated that up to 70% of medical devices in low-income and middle-income countries (LMICs) are partially or completely non-functional due to various factors; donated devices are often designed in and for high-income settings and are not well suited to low-resource settings, and often arrive without manuals or service contracts 7. Furthermore the lack of well-trained biomedical technicians in developing countries to repair the devices when they do inevitably break down exacerbates the problem of unavailability or non-functionality of medical equipment, which has been linked to poor processes of care, impaired service provision and poor patient outcomes 7–11. In Kenya, a survey of 22 secondary referral hospitals found that equipment required to undertake a caesarean section were available in 77%–91% (n=22) of the facilities.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that up to 70% of medical devices in low-income and middle-income countries (LMICs) are partially or completely non-functional due to various factors; donated devices are often designed in and for high-income settings and are not well suited to low-resource settings, and often arrive without manuals or service contracts 7. Furthermore the lack of well-trained biomedical technicians in developing countries to repair the devices when they do inevitably break down exacerbates the problem of unavailability or non-functionality of medical equipment, which has been linked to poor processes of care, impaired service provision and poor patient outcomes 7–11. In Kenya, a survey of 22 secondary referral hospitals found that equipment required to undertake a caesarean section were available in 77%–91% (n=22) of the facilities.…”
Section: Introductionmentioning
confidence: 99%
“…Given the widespread use of smartphones in LMICs, we believe that online educational content accessible from smartphones may prove effective. For instance, a smartphone-based application that provides a step-by-step troubleshooting guide was shown to support BMEs in terms of repairing medical equipment in Ethiopia (9) .…”
Section: Recommendations Based On Japan’s Experiencesmentioning
confidence: 99%
“…The inference method is a part of an expert system that provides a mechanism for the function of thinking and patterns of reasoning used by an expert. This approach discovers the best answers and conclusions for question analysis following the database rules based on facts [5], [6], [9], [21], [22]. Expert systems for clustering the damage to an autonomous motorcycle have been developed in prior studies utilizing the K-means method and the findings of decision tree-based rules (decision tree) [23].…”
Section: Introductionmentioning
confidence: 99%